2020
DOI: 10.1002/jat.3966
|View full text |Cite
|
Sign up to set email alerts
|

Andiroba oil (Carapa guianensisAubl) shows cytotoxicity but no mutagenicity in the ACPP02 gastric cancer cell line

Abstract: Andiroba (Carapa guianensis Aubl) is an Amazonian plant whose oil has been widely used in traditional medicine for various purposes, including anti‐inflammation. Research reports indicate that the oil can confer antitumor activity due to the presence of fatty acids, which can directly influence cell death mechanisms. Thus, andiroba oil (AO) has gained interest for its potential to be used in antineoplastic therapies. Here, we report an in vitro analysis of the cytotoxic and mutagenic potential of AO in the gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
4
3
0
Order By: Relevance
“…In the evaluation of the viability of OTE cells via the MTT test, it was shown that the extracts of both Meliaceae and their respective fractions at the dosage tested did not cause toxicity to this cell type, and there was no inhibition of cell proliferation. Interestingly, in the literature, there are reports of cytotoxicity of some species of a b www.nature.com/scientificreports/ Meliaceae that, when used at high doses (1 mg/mL), induced cell death by apoptosis at 24 and 48 h, while lower concentrations (10 µg/mL and 100 µg/mL) did not show a reduction in cell viability 39 as in the present study. The use of cell viability assays is always an effective way to determine biological toxicity when working with plant extracts, and MTT, in general, is the method of choice for in vitro evaluations to detect the harmful effects of natural products 40 in the most distinct cell types.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In the evaluation of the viability of OTE cells via the MTT test, it was shown that the extracts of both Meliaceae and their respective fractions at the dosage tested did not cause toxicity to this cell type, and there was no inhibition of cell proliferation. Interestingly, in the literature, there are reports of cytotoxicity of some species of a b www.nature.com/scientificreports/ Meliaceae that, when used at high doses (1 mg/mL), induced cell death by apoptosis at 24 and 48 h, while lower concentrations (10 µg/mL and 100 µg/mL) did not show a reduction in cell viability 39 as in the present study. The use of cell viability assays is always an effective way to determine biological toxicity when working with plant extracts, and MTT, in general, is the method of choice for in vitro evaluations to detect the harmful effects of natural products 40 in the most distinct cell types.…”
Section: Discussionsupporting
confidence: 62%
“…In the evaluation of the viability of OTE cells via the MTT test, it was shown that the extracts of both Meliaceae and their respective fractions at the dosage tested did not cause toxicity to this cell type, and there was no inhibition of cell proliferation. Interestingly, in the literature, there are reports of cytotoxicity of some species of Meliaceae that, when used at high doses (1 mg/mL), induced cell death by apoptosis at 24 and 48 h, while lower concentrations (10 µg/mL and 100 µg/mL) did not show a reduction in cell viability 39 as in the present study.…”
Section: Discussionsupporting
confidence: 56%
“…30,31,33 The ACP02 cancer cell line has been widely used as a model for the study of gastric cancer. [34][35][36] The cytotoxicity of the SM leaf extract was determined using the colorimetric MTT assay, which measures enzyme activity, predominantly succinate dehydrogenase. 37 The cytotoxicity was probably related to SM pro-oxidant effects in ACP02 cells since it increased intracellular ROS levels after 24 h of treatment at 200 μgÁml À1the same treatment length used in the MTT assay.…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…Andiroba (Carapa guianensis Aubl) is a plant that belongs to the Meliaceae family [30], and it will be found in Amazon region [31][32][33][34], southern Central America, Colombia, Venezuela, Suriname, French Guiana, Brazil, Peru, Paraguay and the Caribbean Islands [35,36]. In Brazil, it's found in North (states of Acre, Amazonas, Amapá, Pará) region [37] and Northeast (Maranhão state) regions [38].…”
Section: Introductionmentioning
confidence: 99%